Spectral graph drawing - Puppe, Thomas (My University, 2005)
We use eigenvectors of several graph related matrices to draw graphs. Layout properties and implementation methods are analyzed. Finally these concepts are adapted to dynamic graph drawing, i.e. drawing graphs that change over time.
Keywords: 510; Graphenzeichnen; Eigenvektor; 05C90